Pendampingan Pembelajaran Bahasa Arab dengan Buku Ghina’ al-’Arabiy Lil-Athfal di TK Muslimat NU Nawa Kartika XIX Majasem - Ashari, Maulana; Siti Khoirun Nabilatuz Zahro; Azizatur Rahmah Harahap; Assyifa Nurul Irwan; Putri Nur Giyawati (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2025)
Arabic plays a vital role in the lives of Muslims, as it is the language of the Qur'an, the primary guideline for worship. However, the lack of engaging learning methods for early childhood hinders the introduction of Arabic. This study aims to introduce Arabic to children through a fun learning medium, the songbook Ghina' al-'Arabiy Lil-Athfal. This research is a community service research project based on simple experiments. The subjects were children of Muslimat NU Nawa Kartika XIX Kindergarten in Ponorogo. Data collection methods included observation, interviews, and documentation. The instruments used were observation guidelines and student response questionnaires. Data were analyzed descriptively and qualitatively. The results showed that the use of Arabic songbooks adapted to early childhood development, accompanied by interactive learning methods and physical movement, can increase children's enthusiasm and motivation in learning Arabic. The conclusion of this study indicates that Arabic song media is effective in introducing Arabic to children in a fun way. The implications of this study are the importance of innovative learning media based on culture and child development in early childhood education, especially in the introduction of foreign languages such as Arabic.